Accelerated shelf-life testing of virgin coconut oil produced by fermentation - Lozano, Richelle Urobio
ABSTRACT This study aims to determine the storage characteristics and establish the shelf life under accelerated temperature conditions of VCO produced by fermentation process. Formation of free fatty acids increased with time and was found to fir the zero order reaction. peroxide formation was slow since the fatty acid composition of VCO is highly saturated. Water activity remained relatively constant while moisture content showed an insignificant (p>0.05) increase throughout the study. Microbiological analyses indicate that the samples are stable with counts of <25 cfu/ml for both TPC and YMC at the start and end of storage. Using Weibull Hazard Analysis, shelf life of VCO from producer A was equal to 49 days at 45°C (%FFA = 0.2094%; peroxide=1.0962 meq/kg oil) and 241 days at 35°C (%FFA=0.3309%; peroxide=1.4305meq/kg oil). VCO from producer B was found to have a shelf life of 300 days at 45°C (%FFA=0.2957%; peroxide=1.5629meq/kg oil) and 332 days at 35°C (%FFA=0.3111%; peroxide=1.2656meq/kg oil). Shelf life plot was constructed to estimate the shelf life at 25°C which corresponded to 1185 and 368 days for VCO samples from Producers A and B, respectively. Q10 value or the temperature accelerating factor was found to be equal to 4.92 for A and 1.11 for B. Hence, the shelf life of VCO produced using the fermentation process is between 1-3 years. The discrepancy can be attributed to the difference in the manufacturing technique by the two producers, the variety, maturity of coconuts used as raw material and difference in packaging material used by both producers. VCO stability may be attributed to its high degree of saturation and low moisture content.